Pendugaan CPUE dan Potensi Maksimum Lestari Ikan Layang Deles (Decapterus macrosoma) yang Didaratkan di PPN Pengambengan, Jembrana - Bali - Puspitha, Ni Luh Putu Ria (Journal of Marine and Aquatic Sciences; Vol 7 No 1 (2021)DO - 10.24843/jmas.2021.v07.i01.p06, 2021)
Layang deles is one of the highest catches landed in PPN Pengambengan. PPN Pengambengan is a strategic fishery port owned by Jembrana with a function as a center or center for marine fisheries landing. Improvement of fishing technology will be related to the problem of abundance or availability of fishery resoure stocks, so it is necessary to study CPUE, MSY and JTB so that they can utilize the resources with optimal but still maintain its preservation in nature. This research has a purpose, which is to know the trend of CPUE, MSY and JTB of layang deles fish ( Decapterus macrosoma ) landed in PPN Pengambengan. The method used is a quantitative descriptive method using a surplus production analysis from Schaefer. The data used in this study are catch and fleet data from 2014 – 2019 obtained directly from the PPN Pengambengan office. The results showed the highest CPUE in 2015 amounted to 6,12 tons/fleet, but after that the CPUE trend tended to decline, especially since 2016 while the MSY value was obtained at 3.348,9 tons/year with a maximum sustained effort of 1.830 fleets/year. Furthermore, the JTB value is 80% of the MSY value, a figure of 2.679,12 tons/year is obtained. This indicates overfishing and over-exploitation in the PPN Pengambengan area. To prevent overfishing and over-exploitation, prevention can be done, such as limiting fishing capacity and effort can also apply fisheries management models, such as co-management and EBFM (eco-based fisheries management).